Genetic changes in muscle protein following hybridization between Haliotis diversicolor reeve Japan and Taiwan populations revealed using a proteomic approach. Issue 5 (24th January 2013) - Di, Guilan; You, Weiwei; Yu, Jinjin; Wang, Dexiang; Ke, Caihuan
<x xml:space="preserve">Abstract</x> Protein expression patterns were compared in a Japan and Taiwan population of Haliotis diversicolor and in a hybrid between them using 2DE and MALDI‐TOF‐TOF analyses. Using the software PDQuest, 924 ± 7 protein spots were detected in the Japan population (RR), 861 ± 11 in the Taiwan population (TT), and 882 ± 9 in the F1 hybrid (TR). RR and TR were clustered together, but the distance between RR and TT was the maximum using hierarchical cluster analysis. A total of 46 gel spots were identified and a total of 15 spots matched with abalone proteins (a 33.6% identification rate). Hybrid exhibiting additivity or overdominance accounted for 73.9% of these 46 identified proteins. The 46 differentially expressed proteins were shown to be involved in major biological processes, including muscle contraction and regulation, energy metabolism, and stress response. The proteins involved in energy metabolism included adenosine triphosphate (ATP) synthase β subunit, fructose 1, 6‐bisphosphate aldolase, triosephosphate isomerase, enolase, arginine kinase, and tauropine dehydrogenase. These proteins exhibited additivity in their offspring. The proteins involved in stress responses included HSP Hsp70 (exhibiting overdominance in the offspring) and Cu/Zn‐superoxide dismutase (exhibiting additivity). These results suggested that proteomic approach is suitable for analysis of heterosis and functional prediction of abalone hybridization.